Correlation in Stemness-Like State of Ehrlich Carcinoma Cells and Number of Freeze-Thawing Cycles - Diabina, Olga A.; Vinnik, Yuriy A.; Ostankov, Maksim V.; Bondarovich, Nikolay A.; Goltsev, Anatoliy N. (Problems of Cryobiology and Cryomedicine, 2015)
N/A